Harga, Kualitas Pelayanan, Citra Merek dan Kepuasan Pelanggan Pengguna Jasa Transportasi Online - Ghufron Ulinuha (Universitas Pendidikan Nasional, 2021)
This study aims to determine: (1) the effect of price on customer satisfaction, (2) the effect of service quality on customer satisfaction, (3) the effect of brand image on customer satisfaction, and (4) the influence of price, service quality, and brand image on satisfaction. customer. This research is a quantitative research. The population in this study are all customers who use online ojek transportation Grab in Magelang City. The sampling technique used purposive sampling with a total sample of 100 people. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regression. The results of the study indicate that: (1) there is a positive and significant effect of price on customer satisfaction (2) there is a positive and insignificant effect of service quality on customer satisfaction, (3) there is a positive and significant effect of brand image on customer satisfaction (4) there is an influence service quality, price perception, and brand image simultaneously on customer satisfaction.